THE DIFFERENCE IN YOUTH EMOTIONAL COMPETENCY LEVEL BETWEEN GENDER, AND INSTITUTES, TUNAS BAKTI, SECONDARY SCHOOL AND UNIVERSITY STUDENTS - Asma Perveen; Hazalizah Hamzah; Pau Kee; Nurul Ain Hidayah Abas; Azizah Othman; Ebru Morgul; Nurul Ain Mohd Daud (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Many researches have concluded that low level of emotional intelligence can contribute to problems among adolescent. The aim of the study is to explore the emotional issues of youths in the Malaysian context and to investigate the difference in emotional intelligence based on age, gender, and the different institutions. Youths were enrolled from three different institutes, Tunas Bakti school students, secondary school students, and university students. This study consists of 262 youths aged between 13-22 years old were chosen through purposive sampling. The participants were purposively chosen from Tunas Bakti school, secondary school, and university students. Each of them answered the Universiti Sains Malaysia Emotional Quotient Inventory (USMEQ-i). The survey revealed that most students scored average in all emotional subscales. However, the majority of them scored high in the emotional expression subscale. The t-test showed that females scored better in self-awareness, social awareness and relationship management. However, there was no significant difference between gender and any of the self-management subscales and the overall emotional intelligence scores. ANOVA revealed that there was no difference in emotional intelligence between the Tunas Bakti school, secondary school, and university students. This study highlighted the need to develop a module as the emotional competency is a significant need for youngsters. Future studies can help conduct a developmental study to investigate the emotional issues faced by toddlers and children in Malaysia.